Central Bank digital currencies: A framework for assessing why and how - Ben Siu-cheong Fung; Hanna Halaburda (Bank of Canada, 2016)
Digital currencies have attracted strong interest in recent years and have the potential to become widely adopted for use in making payments. Public authorities and central banks around the world are closely monitoring developments in digital currencies and studying their implications for the economy, the financial system and central banks. One key policy question for public authorities such as a central bank is whether or not to issue its own digital currency that can be used by the general public to make payments. There are several public policy arguments for a central-bank-issued digital currency. This paper proposes a framework for assessing why a central bank should consider issuing a digital currency and how to implement it to improve the efficiency of the retail payment system.
Keywords: E41; E42; 330; E-money; Financial Services; Payment clearing and settlement systems